Checklist of Cerambycidae, Disteniidae and Vesperidae (Coleoptera) primary types of the Museu de Zoologia, Universidade de São Paulo, São Paulo, Brazil - Monné, Miguel A.; Santos-Silva, Antonio; Casari, Sônia A.; Monné, Marcela L. (Zootaxa, 2017)
A checklist of the 1164 primary types of Cerambycidae, Disteniidae and Vesperidae (Coleoptera) deposited in the Museu de Zoologia, Universidade de São Paulo, São Paulo, Brazil is provided. Lectotype designations for 97 species are proposed.